Improvement of outcome prediction of hospitalized patients with COVID-19 by a dual marker strategy using high-sensitive cardiac troponin I and copeptin - Kaufmann, Christoph C.; Ahmed, Amro; Kassem, Mona; Freynhofer, Matthias K.; Jäger, Bernhard; Aicher, Gabriele; Equiluz-Bruck, Susanne; Spiel, Alexander O.; Vafai-Tabrizi, Florian; Gschwantler, Michael; Fasching, Peter; Wojta, Johann; et al. (Clinical research in cardiology, 2022)
COVID-19 has been associated with a high prevalence of myocardial injury and increased cardiovascular morbidity. Copeptin, a marker of vasopressin release, has been previously established as a risk marker in both infectious and cardiovascular disease.
Published online: 15 November 2021
Gesehen am 13.04.2022